Performance analysis of Ultra-wideband RF switch using discrete PIN diode in SC-79 package for medical application of microwave imaging - Noor Azwan Shairi; Nursyahirah Mohd Sanusi; Adib Othman; Zahriladha Zakaria; Imran Mohd Ibrahim (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Microwave imaging is an emerging technology in the medical application which have similar functions as X-ray, Magnetic Resonance Imaging (MRI), and Computed Tomography scan (CT scan). In designing a microwave imaging system for medical application, it can use a monostatic radar approach by transmitting a Gaussian pulse (with an ultra-wideband (UWB) frequency). In this system, eight antennas are required with the support of RF switches. Thus, it is important to get the best performance of UWB RF switch in this application. Therefore, this paper presents the performance analysis of four different RF switch topologies (Design 1, 2, 3 and 4) using discrete PIN diode in SC-79 package. The design was based on single pole double throw (SPDT) switch. As result, Design 2 is the best topology after considering the tradeoff between isolation and return loss performances. Based on the three cascaded SPDT switches of Design 2, the insertion loss was less than -2 dB and return loss was more than -10 dB. Meanwhile, the isolation bandwidth (at the minimum isolation of -20 dB) was from 0.5 to 3.7 GHz (with 3.2 GHz bandwidth), hence, it could be used in the UWB frequency for medical application of microwave imaging.